Etika Bisnis Islam Dan Prinsip Keberlanjutan - Lutfi Nuraini (Institut Agama Islam Yasni Bungo Jambi, Indonesia, 2025)
This study aims to explain the importance of integrating Islamic ethical values ​​with sustainability principles as a strategic step in building an ethical and sustainable business model. Islamic business ethics prioritizes the values ​​of justice, honesty, social responsibility, and respect for the rights of all parties involved in economic activities. The principle of sustainability demands the creation of a balance between economic, social, and environmental aspects so that businesses are not only oriented towards financial profit, but also provide long-term benefits for the surrounding community and environment. The study method uses a literature study approach to reputable books and academic journals. The results of the study indicate that the implementation of sustainable Islamic business ethics can improve reputation and consumer trust while supporting fair and environmentally friendly economic development. Islamic business ethics are moral guidelines based on the Qur'an and Hadith that regulate the behavior of business actors to remain in accordance with sharia and able to maintain justice in economic activities. The principle of sustainability in Islamic business ethics emphasizes the importance of balance between economic profit, social welfare, and environmental preservation. The implementation of sustainable Islamic business ethics will help create businesses that are not only profitable but also bring blessings and positive contributions to the surrounding community and environment. This study examines the concepts of Islamic business ethics and sustainability principles, as well as their implications for the modern business world. In conclusion, Islamic business ethics and sustainability principles complement each other in creating businesses that bring benefits and blessings.